2018
DOI: 10.1089/met.2018.0014
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Is Associated with Cognitive Decline in Middle-Aged Patients

Abstract: Background: Diabetes is a major contributor to dementia in the elderly. Identifying mild cognitive decline in younger individuals with diabetes could aid in preventing the progression of the disease. The aim of our study is to compare whether patients with diabetes experience greater cognitive decline than those without diabetes. Methods: We conducted a cross-sectional study using population-based recruitment to identify a cohort of individuals with diabetes and corresponding control group without diabetes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The downregulation of such receptors also causes alterations in the amyloid metabolism and thus amyloid deposition. 14 The control group, when assessed using 3MS, scored significantly higher than patients with the diabetes. According to a systematic review, similar results were found when using 3MS and other cognitive batteries.…”
Section: Discussionmentioning
confidence: 90%
“…The downregulation of such receptors also causes alterations in the amyloid metabolism and thus amyloid deposition. 14 The control group, when assessed using 3MS, scored significantly higher than patients with the diabetes. According to a systematic review, similar results were found when using 3MS and other cognitive batteries.…”
Section: Discussionmentioning
confidence: 90%
“…This is not an entirely novel finding in the literature [ 24 , 25 ]; however, the perspective in the literature, when it comes to correlations between disease states and cognitive function, is quite narrow. For example, studies often illustrate the differences in cognitive outcomes, depending on singular inflammatory conditions, such as diabetes [ 26 ], metabolic syndrome [ 27 ], obstructive sleep apnea [ 28 ], and hypertension [ 14 , 29 ], rather than a collective burden of multiple comorbid conditions. Therefore, this study moves beyond viewing stroke patients as having singular comorbidities, which is less common than those with multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%